Community Empowerment Through Moringa-Based Solid Bath Soap Production Training in Triharjo Village, Lampung - Suryaneta Suryaneta; Tri Noviantoro; Illyyin Nasira; Aurellia Azzahra Mahardika; Anis Azizah; Deviana Safitri; Putri Ananda Nieyan (Community Development Journal, 2026)
This community engagement program addressed the limited value-added utilization of moringa in Triharjo Village, Merbau Mataram Subdistrict, South Lampung Regency, Lampung Province, by providing practical training on producing moringa-based solid bath soap as a household product with economic potential. The program aimed to improve participants’ knowledge and hands-on competence in safe soap-making, introduce a simple standardized procedure, and strengthen readiness for small-scale entrepreneurship. The activity began with coordination and needs identification with local stakeholders, followed by an interactive session on ingredients, safety, and basic formulation principles, and a guided workshop to produce solid soap using moringa powder. Post-training assistance was provided during molding, cutting, curing, and simple packaging. Evaluation used pre-activity and post-activity knowledge tests (30 participants), participant feedback, and basic product observations including appearance, aroma, texture, and acidity level after curing. Results indicated substantial knowledge improvement, with average correctness increasing from 51.1 percent to 86.7 percent, alongside increased participant confidence to reproduce the process independently. The training also resulted in feasible soap bar prototypes with homogeneous appearance and acceptable sensory characteristics for household use. In conclusion, moringa-based solid soap training effectively strengthened community capacity and produced a feasible prototype product, supporting follow-up mentoring toward consistent quality, improved packaging, and sustainable community-based microenterprise development.